A Last Interview with Lewis Aron (Introduction). Issue 3 (2nd September 2022) - Ortúzar, Bárbara; Kuchuck, Steven
Abstract : Steven Kuchuck and Bárbara Ortúzar introduce the transcription of Ortuzar's interview with Lewis Aron at the 2018 Annual IARPP Conference in New York City, Aron's last before his untimely death eight months later.